Baterías con impacto: producción de batería de dos temas inéditos, en base a un análisis de sonoridad de batería de dos temas del disco the Slow Rush de tame Impala - Noboa Woolfson, Daniel Ramiro (2021)
Baterías con Impact, starts off from an investigation of Kevin Parker’s drum recording and production process. The development of this work answers to a need of getting deep insight on a very modern and different sound approach…